Plasmon induced thermoelectric effect in graphene - Viktoryia Shautsova (Nature Portfolio, 2018)
The photoresponse of graphene-based photodetectors is dominated by photovoltaic and photothermoelectric effects. Here, the authors leverage strongly localised plasmonic heating of graphene carriers to detect a second photothermoelectric effect occurring across a homogeneous channel in the presence of an electronic temperature gradient.